Effectiveness of interventions to support the early detection of skin cancer through skin self‐examination: a systematic review and meta‐analysis3. (14th February 2019) - Ersser, S.J.; Effah, A.; Dyson, J.; Kellar, I.; Thomas, S.; McNichol, E.; Caperon, E.; Hewitt, C.; Muinonen‐Martin, A.J.
Summary: Background: As skin cancer incidence rises, there is a need to evaluate early detection interventions by the public using skin self‐examination (SSE); however, the literature focuses on primary prevention. No systematic reviews have evaluated the effectiveness of such SSE interventions. Objectives: To systematically examine, map, appraise and synthesize, qualitatively and quantitatively, studies evaluating the early detection of skin cancer, using SSE interventions. Methods: This is a systematic review (narrative synthesis and meta‐analysis) examining randomized controlled trials (RCTs) and quasiexperimental, observational and qualitative studies, published in English, using PRISMA and National Institute for Health and Care Excellence guidance. The MEDLINE, Embase and PsycINFO databases were searched through to April 2015 (updated in April 2018 using MEDLINE). Risk‐of‐bias assessment was conducted. Results: Included studies ( n = 18), totalling 6836 participants, were derived from 22 papers; these included 12 RCTs and five quasiexperiments and one complex‐intervention development. More studies ( n = 10) focused on targeting high‐risk groups (surveillance) than those at no higher risk (screening) ( n = 8). Ten (45%) study interventions were theoretically underpinned. All of the study outcomes were self‐reported, behaviour related and nonclinical in nature. Meta‐analysis demonstrated the impact of the intervention on the degree of SSE activity from five studies, especially in the short term (up to 4 months) (odds ratio 2·31, 95% confidence interval 1·90–2·82), but with small effect sizes. Risk‐of‐bias assessment indicated that 61% of the studies ( n = 11) were of weak quality. Conclusions: Four RCTs and a quasiexperimental study indicate that some interventions can enhance SSE activity and so are more likely to aid early detection of skin cancer. However, the actual clinical impact remains unclear, and this is based on overall weak study (evidence) quality. Abstract : What's already known about this topic? Few skin self‐examination (SSE) intervention development and evaluation studies have been identified to aid early detection of skin cancer, and no systematic reviews or meta‐analyses have been undertaken. SSE interventions employ varied delivery elements including technological, written and face‐to‐face material. Interventions focus on identifying melanoma and nonmelanoma skin cancer in the population and among high‐risk groups. Evaluative studies currently utilize only self‐reported outcome measures, including knowledge and self‐efficacy, in conducting SSE. What does this study add? Few SSE intervention evaluation studies have a low risk of bias. More studies employed interventions focused on surveillance, targeting those at higher risk, compared with screening SSE practices, for those at no increased risk of skin cancer. Interventions can effectively increase SSE behaviour, but few are underpinned by behaviour change theory. There is a need to promote structured SSE, but we require more theory‐based interventions and rigorously designed studies to evaluate their clinical impact. Linked Comment: Janda. Br J Dermatol 2019;180 :1285 . Plain language summary available online